Narrativa transmedia: del amor al odio casos de violencia en la provincia de El Oro - Ortega Gonzaález, Jonathan Wagner; Ramón Román, Yuliana Estefanía (Machala, 2021)
This paper deals with a problem that today remains a media issue and of social interest, violence against women. A communication proposal through the transmedia narrative to sensitize citizens about violence against women in the province of El Oro. This will be addressed through the creation of communication products which will allow us to reach our audience through an interface and a narrative. In the country there are several organizations, support groups, foundations that create campaigns to try to lower the rates of violence in homes. Although there are campaigns, the rates of violence against women increased due to the pandemic that hit everyone in 2020, where aggressors attacked their partner not only verbally, but also physically and due to the confinement it was also possible to visualize the economic violence due to the lack of employment since it did not allow to have income for the household and thus be able to support basic services. This work is aimed at the development of the transmedia narrative, due to an investigation where the cases of violence against women, causes and consequences were identified. For that we interviewed violent and violent people to be able to know about each of the stories and thus approach them directly from reality, also interviews with professionals such as: Audiovisual Producers, Social Communicators, experts in Narrative and Journalists who were fundamental to create the transmedia narrative. While the focus groups served to identify the right platforms for the dissemination of communication products. The type of methodology that was applied was qualitative,since the following instruments were used: interviews with experts, interviews with victims and perpetrators of violence, group foci, participatory observation and documentary reviews. Through the execution of this research, there was the intervention of professionals in transmedia narrative and visual production, as well as the collaboration of experts in issues of violence. The research design is non-experimental because there was no manipulation of the variable, but we observed this problem as it occurs in society. And it has a non-probabilistic sampling, because there is no record of the audience, with this transmedia narrative it is intended to sensitize the audience, in addition to becoming emitters that help understanding and awareness. Of the products that were made, under a research process in order to be able to carry good products and have a good scope to sensitize people, obtaining good results so doing this type of projects is very rewarding to be able to seek to help in these issues of violence, where everyone is exposed to be victims and help raise awareness. This project was carried out to capture through testimonies the reality that women live in their homes and that this is the beginning so that this project remains as reference material for future research so that transmedia proposals on social problems continue to be made.
El presente trabajo trata de una problemática que hoy en día sigue siendo un tema mediático y de interés social, la violencia contra la mujer. Una propuesta comunicacional mediante la narrativa transmedia para sensibilizar a la ciudadanía sobre la violencia contra la mujer en la provincia de El Oro. Esto será abordado mediante la creación de productos comunicacionales lo cual permitirá llegar a nuestro público por medio de una interfaz y una narrativa. En el país existen varias organizaciones, grupos de apoyo, fundaciones que crean campañas para tratar de bajar los índices de violencia en los hogares. Pese a que existen campañas, los índices de violencia contra la mujer incrementó debido a la pandemia que golpeó a todo el mundo en el año 2020, donde agresores atacaban a su pareja no solo de forma verbal, también física y debido al confinamiento también se pudo visualizar la violencia económica por la falta de empleo ya que no permitía tener ingresos para el hogar y así poder sustentar los servicios básicos. Este trabajo está dirigido para el desarrollo de la narrativa transmedia, debido a una investigación donde se identificó los casos de violencia contra la mujer, causas y consecuencias. Para eso entrevistamos a personas violentas y violentadas para poder conocer sobre cada una de las historias y así abordarlas directamente desde la realidad, también entrevistas a profesionales como: Productores audiovisuales, Comunicadores Sociales, expertos en Narrativa y Periodistas quienes fueron fundamentales para crear la narrativa transmedia. Mientras que los grupos focales sirvieron para poder identificar las plataformas correctas para la difusión de los productos comunicacionales. El tipo de metodología que se aplicó fue cualitativo, ya que se utilizó los siguientes instrumentos: entrevistas a expertos, entrevistas a personas víctimas y victimarios de violencia, focos grupales, observación participativa y revisiones documentales. Mediante la ejecución de esta investigación se contó con la intervención de profesionales en narrativa transmedia y producción visual, de igual manera la colaboración de expertos en temas de violencia. El diseño de investigación es el no experimental porque no hubo ningún tipo de manipulación de la variable, sino que observamos este problema tal y como se da en la sociedad. Y tiene un muestreo no probabilístico, debido que no se cuenta con un registro de la audiencia, con esta narrativa transmedia se pretende sensibilizar a la audiencia, además que se conviertan en emisores que ayuden a la comprensión y sensibilización. De los productos que se realizó, bajo un proceso de investigación para así poder llevar buenos productos y tener un buen alcance para sensibilizar a las personas, obteniendo buenos resultados por eso hacer este tipo de proyectos es muy gratificante para poder buscar ayudar en estos temas de violencia, donde todos están expuestos a ser víctimas y ayudar a crear conciencia. Este proyecto se lo realizó para dejar plasmado mediante testimonios la realidad que viven mujeres en sus hogares y que este sea el inicio para que este proyecto quede como material de referencia para futuras investigaciones para que sigan realizado propuestas transmedia sobre problemas sociales.
Keywords: VIOLENCIA; NARRATIVA; TRANSMEDIA